PROFESSIONAL ORIENTATION OF TEACHING MATHEMATICS AT SCHOOL - Хуршида Устаджалилова (Modern American Journals, 2026)
The article shows the professional orientation of teaching mathematics at school, solving practical problems related to the knowledge of some specific mathematical models from the field of economics, the ability to translate conditions formulated in the form of a text into equations and inequalities.
Keywords: Economic problem, mathematical model, finance, mathematical methods, rational solution, calculations.